Organizational Culture, Leadership, and Competency on Job Satisfaction and Employees Performance at the Public Works and Spatial Planning Office of Pekanbaru - Harry Patuan Panjaitan; Muhammad Awal; Dadi Komardi; Dominicus Josephus Swanto Tjahjana; Intan Purnama (International Conference on Business Management and Accounting, 2023)
This study aims to analyze the influence of organizational culture, leadership, and competence on job satisfaction and employee performance at the Department of Public Works and Spatial Planning in Pekanbaru City. This research is quantitative research by distributing questionnaires to respondents. The sample selection method in this study used the census method so the sample in this study was 78 respondents. Data analysis used Structural Equation Modeling (SEM) using the SmartPLS 3 application. The results of this study indicate that organizational culture has a positive and significant effect on job satisfaction, leadership has a positive and significant effect on job satisfaction, competence has a positive and significant effect on job satisfaction, organizational culture has an effect not significant to employee performance, leadership has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance and job satisfaction has a positive and significant effect on employee performance.